Accounting Recognition and Measurement Theory: A Conceptual and Empirical Comparison of Historical Cost and Fair Value - Enjelina Simarmata Enjelina; Nadia Marintan Sirait; Daniel Partogi Simanjuntak; Dwiky Emanuel Tampubolon; Hicca Maria Gandi Putri Aruan (Manunggal Halim Jaya, 2026)
This study aims to examine the conceptual and empirical debate between historical cost and fair value within the context of accounting recognition and measurement theory. This issue is significant because the measurement basis applied in financial reporting directly influences the quality of accounting information, particularly in terms of relevance and faithful representation. This study adopts a qualitative approach using a structured literature review design. The data consist of secondary sources obtained from reputable journal articles, accounting standards, academic books, and official documents related to financial reporting. The data were analyzed using qualitative content analysis by identifying, classifying, and synthesizing the literature based on the themes of recognition, measurement, historical cost, fair value, relevance, faithful representation, volatility, stewardship, and decision usefulness. The findings indicate that historical cost offers advantages in terms of objectivity, verifiability, stability, and stewardship because it is based on actual transactions that can be objectively verified. However, it has limitations in reflecting current economic values. In contrast, fair value provides greater relevance and decision usefulness because it reflects current market conditions. Nevertheless, it may introduce subjectivity, measurement uncertainty, and volatility in financial statements, particularly when fair values are estimated using unobservable inputs. This study concludes that neither historical cost nor fair value is universally superior. Instead, a mixed measurement model represents a more appropriate approach, as it enables the proportional application of historical cost and fair value according to the characteristics of assets and liabilities, as well as the objectives of financial reporting.